The effect of molar distalization on the maxilla and mandible sagittal relationship - khalil, Fadi (Latakia University Journal -Medical Sciences Series, 2023)
Class II malocclusions is a very common problem, as it constitutes about a quarter to a third of malocclusion cases in the Syrian community, which prompted many researchers to develop appliances to correct this type of malocclusion both dentally and skeletally. Aim: To evaluate changes in the sagittal relationship of the maxilla and mandible before and after the distalization of the upper first molars using both(pendulum) and (2k-loop) distalization appliances. Materials and Methods: This study was designed as a retrospective study, The study sample included (12) patients from the archive of cases of the Department of Orthodontics and orthopedic - Tishreen University, who were treated using both pendulum and 2k-loop distalization appliances, Changes were assessed using lateral cephalometric radiographs of the head. Results: The statistical program (SPSS ver.26. Chicago, IL, USA) was used to perform the necessary statistical analyses, a paired samples T-test was conducted for small independent samples, we obtained a significant decrease in the skeletal classification angel (ANB) by (0.41)°. Conclusions: Both distalization appliances were able to achieve a significant correction of Class II skeletal malocclusion dentally and skeletally, Which means directing the skeletal sagittal relationship of the maxilla and mandible towards first class relationship.